2005
DOI: 10.1128/aac.49.11.4700-4707.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Two Neutralizing Anti-Respiratory Syncytial Virus (RSV) Monoclonal Antibodies in the RSV Murine Model: Time versus Potency

Abstract: Respiratory syncytial virus (RSV) is the leading viral pathogen responsible for bronchiolitis and pneumonia in infants and young children worldwide. We have previously shown in the mouse model that treatment with an anti-RSV neutralizing monoclonal antibody (MAb) against the F glycoprotein of RSV, palivizumab, decreased lung inflammation, airway obstruction, and postmethacholine airway hyperresponsiveness. MEDI-524, or Numax, is a new MAb derived from palivizumab with enhanced neutralizing activity against RSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 33 publications
4
60
0
4
Order By: Relevance
“…Although one would consider this type of correlation obvious, it is not always the case. Notably, the anti-F protein monoclonal antibody palivizumab significantly reduces viral load but does not improve lung histopathology and lung inflammation in the cotton rat RSV model [30]. In the same study, Numax showed better antiviral activity and improvement in lung histopathology than palivizumab.…”
Section: Respiratory Infectionssupporting
confidence: 51%
“…Although one would consider this type of correlation obvious, it is not always the case. Notably, the anti-F protein monoclonal antibody palivizumab significantly reduces viral load but does not improve lung histopathology and lung inflammation in the cotton rat RSV model [30]. In the same study, Numax showed better antiviral activity and improvement in lung histopathology than palivizumab.…”
Section: Respiratory Infectionssupporting
confidence: 51%
“…Neutralizing antibodies can directly block these interactions and lead to reduced numbers of airway infiltrating cells (15,19,27,28). Airway inflammation, initiated either by innate immune responses or neurogenic responses, contribute to development of AHR (29).…”
Section: Cx3cr1mentioning
confidence: 99%
“…31,38,39 In addition, antibody-mediated immunity is relevant for protection against both viruses. 40,41 For example, Palivizumab, an IgG1 humanized anti-F monoclonal antibody, is safe and effective when given in a prophylactic manner to children at risk of severe hRSV infection. 42 Thus, the ideal vaccine for either hRSV or hMPV should provide both antibody and T cell-mediated immune protection.…”
Section: Introductionmentioning
confidence: 99%